2020
DOI: 10.3811/jjmf.2020.010
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Gas Discharge from a Closed End Hole by Using Acoustic Wave Irradiation

Abstract: Filling holes with liquid, or discharging gas from holes, is a fundamental process in both cleaning and painting. Discharging gas from small holes with closed end and high aspect ratio is extremely difficult due to surface tension. In this study, we developed a new gas discharge process from a hole by using acoustic wave irradiation. We irradiated two types of acoustic waves: waves with constant frequencies and those with variable frequencies in time i.e. sweep wave for test samples in a water pool. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…These results suggest that resonance by the second harmonic occurred at 1200 Hz. Note that the removal rate was greater for only 600, not 1200, Hz for speakers with different acoustic characteristics [12]. For these reasons, we observed two peaks in sample one.…”
Section: First Stage Irradiation (Test Two) 421 Air Column Removalmentioning
confidence: 75%
See 1 more Smart Citation
“…These results suggest that resonance by the second harmonic occurred at 1200 Hz. Note that the removal rate was greater for only 600, not 1200, Hz for speakers with different acoustic characteristics [12]. For these reasons, we observed two peaks in sample one.…”
Section: First Stage Irradiation (Test Two) 421 Air Column Removalmentioning
confidence: 75%
“…The repeatedly generated droplet deposition split the gas in the hole. Furuya et al [12] proposed using acoustic wave irradiation in a liquid to remove gas. They showed that releasing part of the gas at specific frequencies (f = 600 Hz) when irradiating with a single-frequency sine wave achieved complete gas removal when the frequency increased monotonically with time.…”
Section: Introductionmentioning
confidence: 99%